Between uncertainty and aspiration: Future expectations of Juvenile Inmates at the Class 1 Correctional Facility for Children in Kupang - Wistya Rullyati Kuntoro; Harnita Erwanda Widyanti Djawa; Stevy Puji Lestari Haning; Marciany Chayaratry Airlangga Putri Tokan; Indra Yohanes Kiling (University of Merdeka Malang, 2024)
ABSTRACTThe present study aimed to explore the future aspirations of children in correctional facilities (Andikpas) at the Kupang Class 1 Special Correctional Institution for Children (LPKA). By understanding their hopes and aspirations, this study seeks to provide insights into the challenges faced by these children in the process of social reintegration. The study also aimed to identify factors influencing their aspirations, including social stigma, institutional support, and family economic conditions. It is crucial to highlight that the future of children in correctional facilities is heavily influenced by a range of interconnected factors. By gaining a better understanding of the aspirations and challenges faced by Andikpas, this study is expected to provide useful recommendations for policymakers, correctional institutions, and the broader community to create a more supportive environment for these children. Comprehensive support from various stakeholders is essential to help them realize their hopes and aspirations after leaving the LPKA.ABSTRACTAspirasi masa depan merupakan aspek penting bagi anak didik pemasyarakatan (Andikpas) di LPKA Klas 1 Kupang, yang sedang menjalani proses reintegrasi sosial. Aspirasi masa depan dapat mempengaruhi motivasi, perilaku, dan kesejahteraan Andikpas. Namun, aspirasi mereka seringkali terhambat oleh berbagai faktor ketidakpastian yang mereka hadapi, seperti stigma sosial, kesulitan ekonomi, akses sumber daya yang terbatas, dukungan keluarga, teman, dan pihak LPKA. Penelitian ini bertujuan untuk mengeksplorasi aspirasi masa depan Andikpas di LPKA Klas 1 Kupang. Penelitian ini mengadopsi pendekatan kualitatif dan menerapkan analisis tematik sebagai metode utama dalam menganalisis data. Data dikumpulkan melalui wawancara dan observasi di LPKA Klas 1 Kupang. Analisis tematik dilakukan untuk mengidentifikasi tema-tema utama yang muncul dari data yang diperoleh dari lima Andikpas yang dipilih secara purposive. Hasil penelitian ini diharapkan dapat memberikan gambaran komprehensif tentang aspirasi masa depan Andikpas dan tantangan yang mereka hadapi. Penelitian ini juga diharapkan dapat memberikan rekomendasi bagi pihak-pihak yang terkait dengan pengembangan dan pembinaan Andikpas.